Size control of gold nanoparticles by electrochemical synthesis - Chia, Vye Rern. (2013)
The purpose of this work is to find out the relationship between the effects of electrochemical parameters on the size of gold nanoparticles, to investigate the possibility of controlling the size of electrochemically synthesized gold nanoparticles. To achieve this aim, electrochemical synthesis was conducted with different varying parameters, and UV-Vis Spectrometry was used to obtain the absorption readings of the samples. These UV-Vis readings were then used to correlated with the nanoparticle size.